Influence of protein/glycan interaction on site‐specific glycan heterogeneity. Issue 10 (5th July 2017) - Losfeld, Marie‐Estelle; Scibona, Ernesto; Lin, Chia‐Wei; Villiger, Thomas K.; Gauss, Robert; Morbidelli, Massimo; Aebi, Markus
ABSTRACT: To study how the interaction between N ‐linked glycans and the surrounding amino acids influences oligosaccharide processing, we used protein disulfide isomerase (PDI), a glycoprotein bearing 5 N ‐glycosylation sites, as a model system and expressed it transiently in a Chinese hamster ovary (CHO)‐S cell line. PDI was produced as both secreted Sec‐PDI and endoplasmic reticulum‐retained glycoprotein (ER)‐PDI, to study glycan processing by ER and Golgi resident enzymes. Quantitative site‐specific glycosylation profiles were obtained, and flux analysis enabled modeling site‐specific glycan processing. By altering the primary sequence of PDI, we changed the glycan/protein interaction and thus the site‐specific glycoprofile because of the improved enzymatic fluxes at enzymatic bottlenecks. Our results highlight the importance of direct interactions between N ‐glycans and surface‐exposed amino acids of glycoproteins on processing in the ER and the Golgi and the possibility of changing a site‐specific N ‐glycan profile by modulating such interactions and thus the associated enzymatic fluxes. Altering the primary protein sequence can therefore be used to glycoengineer recombinant proteins.—Losfeld, M.‐E., Scibona, E., Lin, C.‐W., Villiger, T. K., Gauss, R., Morbidelli, M., Aebi, M. Influence of protein/glycan interaction on site‐specific glycan heterogeneity. FASEB J. 31, 4623‐4635 (2017). www.fasebj.org